Impacts of el nino and la nina on palm oil production: evidence from selected palm oil producing countries - Jalil, Athirah Suhailah; Yan-Ling, Tan (UiTM Cawangan Johor, 2021)
Palm oil is one of the most important edible oils commercialied in world oils and fats market. However, agriculture is highly vulnerable to climate change. For instance, El Nino is the warm phase of El Nino Southern Oscillation (ENSO) while La Nina is the opposite of El Nino, the cold phase of ENSO. Strong El Nino and La Nina events cause global changes especially in temperature and rainfall, subsequently affect agricultural areas and causing considerable economic losses. Therefore, the objective of this study is to explore the impacts of El Nino and La Nina on palm oil production in selected palm oil producing countries namely Indonesia, Malaysia and Thailand from 1980 to 2019 using the Ordinary Least Square (OLS) multiple regression analysis. The results revealed that area han1ested and palm oil price affect palm oil production significantly in all palm oil producing countries. Nevertheless, the ENSO effects are not apparent. Only the El Nino dummy coefficients are negative and statistically significant in Thailand, suggesting that the occurrence of El Nino events is more pronounced than the La Nina events on palm oil production in Thailand. Hence, this study suggests that a good water management system is needed to allow the palm oil to achieve optimum production.